Neo-nationalism and Universities : Populists, Autocrats, and the Future of Higher Education - Douglass, John Aubrey (Book collections on Project MUSE., 2021)
"This book offers the first significant examination of the rise of neo-nationalism and its impact on the missions, activities, behaviors, and productivity of leading national universities. This book also presents the first major comparative exploration of the role of national politics and norms in shaping the role of universities in nation-states, and vice versa, and discusses when universities are societal leaders or followers-in promoting a civil society, facilitating talent mobility, in researching challenging social problems, or in reinforcing and supporting an existing social and political order"--